2019
DOI: 10.1088/1742-6596/1386/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Removal of rhodamine B in wastewater from the textile industry using geopolymeric material

Abstract: In this work a geopolymeric material was synthesized by alkaline activation of calcined coal gangue at 700 °C using a solution 1:9 of NaOH:Na2SiO3, as a sorbent to remove rhodamine B from aqueous solutions. X-ray diffraction, fourier-transform infrared spectroscopy and scanning electron microscopy were used to characterize the material structurally and morphologically; removal efficiency and rhodamine B sorption capacity were evaluated by using ultraviolet-visible spectrophotometry. Sorption tests were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…With Rhodamine B as the removal target, using geopolymers as adsorbents, the removal capacity was increased as the contact time increased, allowing the active sites to interact more fully with the dye molecules. However, this experiment also showed that when the contact time exceeded a certain critical time, the adsorption capacity stopped increasing [ 101 ]. Activated geopolymer with a specific surface area of 35.7 m 2 /g was used for the adsorption of methyl orange (MO) dye, but the experimental results showed that compared to kaolinite and metakaolinite, activated geopolymer had the largest specific surface area, but the adsorption effect was lower than the other two substances.…”
Section: Application Of Geopolymers In Adsorptionmentioning
confidence: 99%
“…With Rhodamine B as the removal target, using geopolymers as adsorbents, the removal capacity was increased as the contact time increased, allowing the active sites to interact more fully with the dye molecules. However, this experiment also showed that when the contact time exceeded a certain critical time, the adsorption capacity stopped increasing [ 101 ]. Activated geopolymer with a specific surface area of 35.7 m 2 /g was used for the adsorption of methyl orange (MO) dye, but the experimental results showed that compared to kaolinite and metakaolinite, activated geopolymer had the largest specific surface area, but the adsorption effect was lower than the other two substances.…”
Section: Application Of Geopolymers In Adsorptionmentioning
confidence: 99%
“…Depending on the ratio of Si/Al, the geopolymers are classified into three types of three-dimensional network structures, such as polysialate (–O–Si–O–Al–O–), polysialate siloxo (–O–Si–O–Al–O–Si–O–), and polysialate disiloxo (O–Si–O–Al–O–Si–O–Si–O–). As seen, the initial Si/Al ratio in the starting material could be the decisive factor in terms of the mechanical strength of the conducted geopolymer, which typically ranges from 3.0 to 3.8. , Preparation and characterization of geopolymers with different synthesis conditions and adsorption applications have been carried out in many studies. Usually, initial materials with high SiO 2 and Al 2 O 3 content are favored for the geopolymerization . During the formation process, in the presence of the materials, active substances such as high concentrations of alkali-metal solutions and binders such as sodium silicate (e.g., Na 2 SiO 3 ) would be added to the mixture .…”
Section: Introductionmentioning
confidence: 99%
“…15 , 16 Preparation and characterization of geopolymers with different synthesis conditions and adsorption applications have been carried out in many studies. 17 22 Usually, initial materials with high SiO 2 and Al 2 O 3 content are favored for the geopolymerization. 23 During the formation process, in the presence of the materials, active substances such as high concentrations of alkali-metal solutions and binders such as sodium silicate (e.g., Na 2 SiO 3 ) would be added to the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Dyes are important compounds commonly used in various industries, such as textile, paper, leather and plastic manufacturing. The textile industry is a focus of pollution; this industry produces 8000 kg/day per fabric and consumes approximately 1.6 million liters of water per day 1 . The discharge of dye-containing effluent without proper treatment into water causes environmental and health damage.…”
Section: Introductionmentioning
confidence: 99%
“…The initial ratio of Si/Al in the raw material from 3.0 to 3.8 could offer a very important role in the mechanical strength of the conducted geopolymer 8-10 . There are many studies about the preparation and properties of geopolymers with different synthesis conditions and adsorption applications 1,[11][12][13][14][15] . Normally, the starting material with a high content of SiO 2 and Al 2 O 3 is favored for geopolymerization, for example, coal fly ash 16,17 , steel slag 18,19 , rice husk 20 the formation process, the activates, such as highconcentration alkali solution (NaOH, KOH, …) and the binder sodium silicate (Na 2 SiO 3 ), would be added to the mixture in the presence of the material 10 .…”
Section: Introductionmentioning
confidence: 99%